Campus Medius digital mapping in cultural and media studies. (TRANSCRIPT VERLAG, 2022)
Campus Medius explores and expands the possibilities of digital cartography in cultural and media studies. Simon Ganahl documents the development of the project from a historical case study to a mapping platform. Based on the question what a media experience is, the concepts of the apparatus (dispositif) and the actor-network are translated into a data model. A time-space of 24 hours in Vienna in May 1933, marked by a so-called 'Turks Deliverance Celebration' (Türkenbefreiungsfeier), serves as an empirical laboratory. This Austrofascist rally is mapped from multiple perspectives and weaved into media-historical networks, spanning from the seventeenth century up to the present day.